ANALISIS YURIDIS PERJANJIAN EKSTRADISI ANTARA PEMERINTAH REPUBLIK INDONESIA DENGAN PEMERINTAH DIRAJA MALAYSIA (STUDI KASUS: DJOKO SOEGIARTO TJANDRA) - Fikhri Sultan Maulana Fadjar Daulat; Ida Kurnia (Fakultas Hukum Universitas Tarumanagara, 2021)
Along with the increasingly rapid development of the times, crime also develops rapidly. In some cases the crime does not only occur within the country, but also occurs at home and abroad, which of course will involve other countries in its implementation. Crimes involving many countries are known as crimes with international dimensions or can also be referred to as transnational crimes. Therefore, in order to overcome this, the extradition mechanism appears as an institution that is expected to be able to prevent and eradicate crimes with an international dimension quickly and effectively. However, the implementation of the extradition mechanism actually raises various polemics and dilemmas, where many of the cases with an international dimension cannot be resolved by the extradition mechanism, so this makes the existence of the extradition mechanism begin to be questioned, namely whether the extradition mechanism is truly capable of dealing with crimes with international dimensions. Therefore, it is necessary to carry out an in-depth analysis and study to find out the causes of the inability of the extradition mechanism to eradicate crimes with an international dimension, so that an evaluation of the extradition mechanism can be carried out so that the fight against crimes with an international dimension will be better in the future.